Spatial data infrastructures at work : analysing the spatial enablement of public sector processes - Dessers, Ezra (Leuven University Press, 2013)
"Spatial data, also known as geospatial data or geographic information, identifies the geographic location of natural and constructed features and boundaries on Earth, and has become increasingly important in various administrative practices. In order to facilitate access, use, and sharing of spatial data among organisations, information is brought together in clustered initiatives known as Spatial Data Infrastructures (SDIS). In this book, Ezra Dessers introduces spatial enablement as a key concept to describe the realisation of SDI objectives in the context of individual public sector processes."
Keywords: prostorová data; geografická data; analýza dat; infrastruktura; spatial data; geographical data; data analysis; infrastructure (economics); studie; studies